Elaboración de una guía didáctica de estrategias y actividades lúdicas para el desarrollo de la autonomía de los niños de primer año de preparatoria - Coronado Ullco, Mikaela Liseth (2022)
This research proposal is based on the design of a pedagogical guide "playing I learn to be independent" for the development of the autonomy of children in the first year of high school, according to the needs of children in the educational and family environment, who will be the main beneficiaries with innovative proposals to achieve self-confident and independent children, the activities will improve their autonomy based on proposed strategies that will support the teacher where he becomes a mediator of information to build learning in children , the activities are based on the initial education curriculum with the game-work method that Maria Montessori used, allowing her to learn adequately, experienced different areas in the educational field, I mention that children are a sponge where they learn what they observe and hear; Children must be able to carry out activities according to their age, using the constructivist methodology that will allow children to learn through learning experiences, achieving significant learning, allowing them to create their own knowledge and development of their autonomy, leaving it clear that most children are overprotected by their parents and are restrained from experiences, responsibilities of daily life, the child learns through practice, to solve real problems where he values and becomes an active person in society who help him strengthen their autonomy and identity. Finally, the activities that are displayed in the guide contain objectives, scope, skills that are evidenced in the initial education curriculum, didactic material was developed that will help the development of abilities and skills, focused so that the child learns to accept himself, to their environment and be able to make decisions, solve problems and face the consequences, each activity contains a checklist that will serve to carry out an evaluation of children and know the progress on autonomy achieving each of the skills, turning independent children in society with critical thinking, the activities were validated with experts, the same ones who guided us when making the guide and consider that they are relevant for the development of autonomy in children's teaching-learning.